THE DUAL FORM OF EDUCATION IN GERMANY: STRUCTURE, DYNAMICS, AND COMPARATIVE ASPECTS OF IMPLEMENTATION IN UKRAINE (Comparative Professional Pedagogy, 2025)
The modernization of higher education in Ukraine necessitates the search for effective models of cooperation between universities and the labor market. One of the most promising formats is dual education, which combines academic learning with practical training in a real working environment. Germany stands out as a leading country in implementing dual study programs at the national level, offering a well-established institutional, legal, and financial framework. This article provides a comprehensive analysis of the structure and typology of dual higher education programs in Germany, including educational levels, types of institutions, fields of study, ownership, and organizational formats (education-integrated, practice-integrated, profession-integrated). The study draws on empirical data from the national database AusbildungPlus, the HRK Hochschulkompass, and a national survey conducted by the CHE Center for Higher Education.Special attention is paid to the financial aspects of dual education, including tuition coverage and the role of employers. The paper also outlines the current status of dual education in Ukraine, noting experimental models, the predominance of technical and agricultural institutions, and challenges related to regulatory clarity and financing. A comparative analysis of the German and Ukrainian contexts highlights both similarities and discrepancies in regulatory frameworks, stakeholder cooperation, and quality assurance mechanisms. Based on Germany’s experience, the article offers key elements for adapting and strengthening dual education in Ukraine, such as defining minimum standards, incentivizing employers, involving them in curriculum development, and creating reliable monitoring systems. It is found that dual education has significant potential to improve the quality of higher education in Ukraine, especially in the context of the need to bring educational outcomes closer to the needs of the labor market. Its development should be based not only on European experience, but also on a deep understanding of the needs of the national education system, the peculiarities of the economy and the specifics of the Ukrainian labor market.
Keywords: dual education; higher education; Germany; Ukraine; university-business cooperation; educational models; quality assurance; policy adaptation